Where do we come from and where are we going? A look to project didactics - Granados Manjarrés, Maritza (Estoa. Journal of the Faculty of Architecture and Urbanism, 2021)
This paper presents a general state of architecture teaching that, crossed by the most used design methodologies, defines project didactics. It proposes that the pedagogy is constructed at the crossroads of a variety of factors of diverse nature. In the first part, a global perspective of these methodologies is presented from 1962 to 2012, and then it reviews how architecture teaching has been in the Latin American context taking into account various pedagogical experiments carried out during the second half of the last century. Finally, the studio is questioned as the main teaching method of the architectural project, a question that is based on the analysis of social media. In the last part, a series of recommendations and improvement strategies are given, but above all, it invites us to think about how to change the status quo of project teaching.